G324 Prevalence of thinness in adolescent girls in low and middle-income countries and associations with national wealth, food security, gender inequity and income inequality: A cross-sectional study. (27th April 2016) - Candler, TP; Costa, S; Heys, M; Costello, A; Viner, R
Abstract : Background: Adequate nutrition during adolescence is important for optimal physical and cognitive development and for pregnancy either during adolescence or later life. Thinness amongst adolescent girls in low and middle income countries (LMIC) has been little studied. Methods: We used BMI data from 40 LMIC from the Global School Health Survey to estimate the prevalence of moderate and severe thinness in 12–18 year olds using the WHO 2007 growth reference. Self-report data on going to bed hungry was used as a proxy for household food insecurity. We used multi-level models to assess whether national wealth (gross domestic product, GDP), income inequality (Gini index), national gender inequality (Gender Inequality Index (GEI)) and food security (Global Food Security Index (GFSI)) were associated with undernutrition. Results: Prevalence rates of moderate and severe thinness across 61, 603 girls from 40 countries were 6.30% (95% CI: 5.71, 6.95) and 1.34% (1.12, 1.59) respectively. The prevalence of combined moderate and severe thinness demonstrated wide variation between countries; countries in Asia were found to have highest prevalence (nearly 20% in Sri Lanka). Combined moderate/severe thinness was more common amongst early (12–14 years) than later adolescents (15–18 years). Going to bed hungry sometimes was associated with increased risk of moderate/severe thinness (OR: 1.102; 95% CI 1.007, 1.206). A significant inverse relationship was found between thinness and GDP (OR: 0.94; 95% CI: 0.88, 0.99) and GFSI (OR: 0.96; 95% CI: 0.93, 0.99) but not Gini or GEI. Conclusion: Thinness is still prevalent in adolescent schoolgirls in LMIC, and poses a significant threat to their health and that of the next generation. New attention is needed to public health nutrition interventions for adolescent girls in LMIC. Our study provides the first systematic data on adolescent thinness to guide regional and national nutrition strategies and provides data to allow for future epidemiological comparisons.